An advanced mobile robot for educational purpose - Scott, Guyan (2018)
The world is calling out for more STEM students and graduates. In order to help provide current students, our future, the needed skills and knowledge to better mankind, the education system must adapt and encompass new technologies and knowledge. The use of robotics and various coding languages are now being rolled in to education systems thought the world at a young age. This project aims to develop a prototype robot, grounded in a raspberry pi, to be used in education for the purpose of teaching and training students about coding and engineering. The main object is to spark interest and passion for a subject which is seeing a decline in the number of students. In order to ensure the robot is best used to promote STEM education it was decided to also produce an interactive lesson plain for students which should be a comprehensive, engaging and exploratory introduction into STEM subjects.